A maximum entropy classification scheme for phishing detection using parsimonious features - Emmanuel O. Asani; Adebayo Omotosho; Paul A. Danquah; Joyce A. Ayoola; Peace O. Ayegba; Olumide B. Longe (Universitas Ahmad Dahlan, 2021)
Over the years, electronic mail (e-mail) has been the target of several malicious attacks. Phishing is one of the most recognizable forms of manipulation aimed at e-mail users and usually, employs social engineering to trick innocent users into supplying sensitive information into an imposter website. Attacks from phishing emails can result in the exposure of confidential information, financial loss, data misuse, and others. This paper presents the implementation of a maximum entropy (ME) classification method for an efficient approach to the identification of phishing emails. Our result showed that maximum entropy with parsimonious feature space gives a better classification precision than both the Naïve Bayes and support vector machine (SVM).